International Portability of Health-Cost Coverage : Concepts and Experience - Werding, Martin; McLennan, Stuart (World Bank, Washington, DC, 2017)
Social insurance and other arrangements for funding health-care benefits often establish long-term relationships, effectively providing insurance against lasting changes in an individual's health status, engaging in burden-smoothing over the life cycle, and entailing additional elements of redistribution. International portability regarding this type of cover is, therefore, difficult to establish, but at the same time rather important both for the individuals affected and for the health funds involved in any instance of an international change in work place or residence. In this paper, full portability of health-cost cover is taken to mean that mobile individuals can, at a minimum, find comparable continuation of coverage under a different system and that this does not impose external costs or benefits on other members of the systems in the source and destination countries. Both of these aspects needs to be addressed in a meaningful portability framework for health systems, as lacking or incomplete portability may not only lead to significant losses in coverage for an individual who considers becoming mobile which may impede mobility that is otherwise likely to be beneficial. It may also lead to financial losses, or windfall gains, for sources of health-cost funding which can ultimately lead to a detrimental process of risk segmentation across national health systems. Against this background, even the most advanced sets of existing portability rules, such as those agreed upon multilaterally at the EU-level or laid down in bilateral agreements on social protection, appear to be untargeted, inconsistent and therefore potentially harmful, either for migrants or for health funds operated at both ends of the migration process, and hence for other individuals who are covered there.